Thread of Influence: Advertisements as Intrusive Narrative on X - Ainut Tuqo, Fina; Miftah Rihhadatul 'Aisy, Choirum; Nabila, Citra; Madinatul Ilmi, Afwi; Adila, Wildi (RADIANT: Journal of Applied, Social, and Education Studies, 2026)
This study aims to explore several types of digital storytelling containing embedded advertising, namely riding the waves, sharing experience, and problem-solution. The data were collected from four X account namely @linskinjournal, @martabakismissu, @kforkinsley, and @glowinbeautyy which are known to frequently incorporating digital storytelling. This study also aims to analyze the level of intrusiveness in digital storytelling based on Nur Aini et al. (2023), which is classified into three types: natural, less natural, and unnatural. This study uses a descriptive qualitative method. The findings show that sharing experience is the type of digital storytelling most often used by accounts to embed advertising as personal storytelling create authenticity. Problem-solution is the second most frequently used type, while riding the wave is the type of digital storytelling that is rarely used to embed advertising. In addition, based on the level of intrusiveness by Nur Aini et al. (2023), embedded advertising on the digital storytelling is most often natural as the accounts tend to promote their product in a way that is closely related to the story being presented. At the same time, less natural embedded advertising also appears in some posts, where the promotional content is slightly disconnected from the main story.